Cultural Differences in People’s Psychological Response to COVID-19 - Yap, Suhui; Lee, Albert; Ji, Li-Jun; Li, Ye; Dong, Ying (Frontiers in Psychology, 2021)
The present research studied Chinese and Euro-Canadian students during the COVID-19 pandemic, focusing on their affect, optimism, well-being, and meaning in life. The results revealed both differences and similarities across cultures. As predicted, Chinese participants reported more positive affect and less negative affect, higher optimism, higher state psychological well-being, and higher meaning presence, compared to Euro-Canadian participants. The findings were replicated after a week’s delay. Analyses on longitudinal data showed that state optimism, state well-being, and meaning presence influenced one another over time. These variables also mediated the cultural differences in one another. These results are consistent with cultural work on naïve dialecticism and non-linear lay theory of change. Results also demonstrate underlying relationships among the constructs that are common to both cultural groups. Broadly, the present research highlights the impact of culture on people’s response to challenging life situations and the mechanisms underlying these cultural differences.